Leaving Before Completing: How Course Withdrawal Predicts College Student Success - Ibrahim Bicak; Z.W. Taylor (Journal of College Orientation, Transition, and Retention)
Course withdrawal is common among college students, but scant empirical research has explored the effects of course withdrawal on student outcomes (e.g., persistence, degree attainment). By using statewide administrative data from Texas (N=605,362), we estimate the relationship between course withdrawal and student outcomes, finding course withdrawal rates usually affect time to degree and degree attainment. We also find that time to degree increases as withdrawal rate increases, as the more students withdraw from courses, the fewer excess credits they accumulate. We also discover nuance in degree attainment, as data suggests a 4% withdrawal rate (about one or two courses withdrawn) may start erosion of a student’s degree progress, evidenced by the data in this study. Moreover, further course withdrawals diminished a student’s probability of earning a degree. We conclude by discussing implications for practice, policy, and future research.